Pengaruh Dukungan Organisasi terhadap Kepuasan Kerja dan Komitmen Organisasi di SD Taman Rama Jimbaran - Ni Wayan Cahya Ayu Pratami; Ni Nyoman Muryatini (Widya Manajemen, 2022)
Organizational commitment is very important in the working field. It is the commitment to show high performance. This organizational commitment is influenced by organizational support and job satisfaction. This study aims to analyze: (1) the effect of organizational support on job satisfaction, (2) the effect of organizational support on organizational commitment, and (3) the effect of job satisfaction on organizational commitment. In this study, the sampling technique used was random sampling and the data were collected using a questionnaire. The technique of analysis used was path analysis. The results of this study were organizational support has positive and significant effects on job satisfaction and organizational commitment, and also job satisfaction has a positive and significant effect on organizational commitment.